ANALISIS PENERAPAN 5S (SEIRI, SEITON, SEISO, SEIKETSU, SHITSUKE) TERHADAP EFEKTIVITAS KERJA PADA TB INDOSATU BATAM - Akbar Rifqi Baharsyah; Sirati, Ganda (LPPM Universitas Putera Batam, 2025)
This research was conducted at TB Indosatu Batam, a building materials retail company, with the aim of analyzing the implementation of the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) on work effectiveness. Problems found in the company’s work environment include a lack of employee discipline, inefficient material arrangement, limited workspace, and poor cleanliness. The research method used was direct implementation of the 5S approach, carried out through initial observation, execution of the 5S program, and evaluation of the results. The findings indicate that systematic application of the 5S method has a positive impact on the work environment. The Seiri stage helped eliminate unnecessary items and optimize space usage. The Seiton stage facilitated easier access to materials through structured organization. The Seiso stage enhanced work comfort through scheduled cleaning. The Seiketsu stage maintained consistency with standardized procedures. The Shitsuke stage fostered a disciplined work culture through training and reward systems. Implementation of the 5S method effectively improved work efficiency, organization of material layout, and created a cleaner, safer, and more productive work environment at TB Indosatu Batam.